RM Silk Screen Contractor a work study - Eiaw, Sherilyn U. (College of Engineering, 1998)
RM Silk Screen Contractor is a contractual manufacturing company which engages in panaflex-making and other signage products. Situated in Sta. Quiteria, Caloocan City, the company prides itself as the sole manufacturer of the panaflex signboards of Video City. The work study group aims to study and improve the panaflex division of the company through the application work study techniques. By analyzing the present organization and system of the company enabled the work study group to diagnose the various problems encountered by the company's internal system. Idle workers, unsafe working conditions, and lack of adequate working sections are among the problems faced by RM Silk Screen Contractor. The work study group has also noticed the effect of a clattered work area, machine breakdown, insufficiency of raw materials and the type of payment scheme have on its workers. All of these problems result to a decrease in productivity and profit of RM Silk Screen Contractor.Through careful analysis of the company's issues, the group has been able to come up with several solutions to its problems. All of the alternatives are screened using work study techniques taught in IE 32. Cost, implementation ease, and the effect on the company are among the factors considered in the analysis of the alternatives. Modification of its production sequence, systems and procedures, inventory control and payment scheme are answers to its idle workers concerns. Proposals of artificial ventilation, shelf,table, and safety measures are also made to improve the working conditions within the company.